Teachers' Reflections in Teaching English Vocabulary for Students with Disabilities: A Descriptive Study - Suhaimah, Ade Fairuz; Yusra, Siti Rahimah (Journal of Authentic Research, 2026)
This qualitative descriptive multi-site study examined how three English teachers retrospectively interpreted and adapted vocabulary instruction in one Indonesian special school and one inclusive vocational school. One participant was a special-education graduate teaching learners with intellectual disabilities; two were English-education graduates teaching mixed-ability classes that included learners described by the school as ‘slow learners,’ a classification that was not verified through diagnostic records. Data consisted of five-prompt reflective journals written in Indonesian. Analysis combined inductive coding with an analytic distinction among event description, interpretation of learner response, justification of an instructional decision, evaluation of perceived consequences, and planning for future action. Member checking was limited to participants’ own accounts rather than the final themes. The results showed contextual differences. T1 emphasized pronunciation barriers and repeated multimodal practice; T2 emphasized differentiated materials and proposed consultation with counselors and vocational teachers; T3 emphasized extended processing time, active participation, and patience. Across cases, the teachers described a provisional sequence of noticing a barrier, interpreting learner response, modifying support, appraising the perceived response, and planning subsequent action. Not every account contained all stages, and the reported benefits were not independently verified. The study’s primary contribution is a context-specific account of how retrospective reflection connected learner variability with instructional differentiation across two settings, rather than evidence that particular techniques were effective. Conclusions are limited by the small purposive sample, self-report data, uncertain learner classification at the inclusive site, single-researcher coding, translation, and the absence of observation, interviews, student work, or direct learning measures.